Akal dan Otak dalam Al-Qur’an dan Neurosains Serta Relefansinya terhadap Pendidikan Islam (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
Concepts of reason, brain, and the Qur'an in neuroscience, intelligence is among human capacities in which goals are tools and a pair of knowledge scales to understand right and wrong. Intelligence in the Qur'an can be intended as a medium to think about Allah's authorization and creation in all circumstances. Intellect is part of the greatest gift. It will be given by Allah to humans as creatures who have the highest position in the eyes of Allah. Anatomically, the brain can be divided into several parts according to their respective roles and functions. Whereas Neuroscience and how it relates to Islamic education. Referring to the study that Islamic education only discusses the aspect of thought (reason), one indication is that Islamic religious learning is only in the doctrinal pedagogical part and not rational and empirical. As a result, Islamic education has not been able to develop the potential of the brain that exists in students to become superior human beings, where human excellence is determined by their mind/reason or brain.